Nano-Preyssler Heteropolyacid: A Novel Nanocatalyst for Poly-Condensation of Benzyl Alcohols - F. Bamoharram, Fatemeh (Asian Journal of Chemistry, 2010)
Silica-supported preyssler nanoparticles, behave as an effective nanocatalyst in poly-condensation of benzyl alcohol and its derivates. The polymer is characterized by 1H NMR, IR and UV-vis spectroscopy.